Mof-ldhs heterostructure catalyst and preparation method and application thereof

CN122942101APending Publication Date: 2026-10-20FOSHAN XIANHU LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611120103.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有NiFe基催化剂在工业电流密度下仍存在反应动力学不足、活性位点利用率有限、Cl-竞争吸附和腐蚀导致稳定性下降等问题

Benefits of technology

(1)本发明基于金属有机框架材料(MOF),尤其是由有机羧酸配体与Ni、Fe金属位点配位形成的NiFe-MOF,具有结构可调、比表面积大、金属中心分散度高和配位环境可设计等特点;同时NiFe-LDHs具有较好的碱性OER活性和结构稳定性;本发明利用有机羧酸配体在温和条件下诱导NiFe合金表面金属位点配位重构,并进一步形成由NiFe-MOF与NiFe-LDHs耦合的异质结构,制得NiFe-MOF/NiFe-LDHs异质结构催化剂,能够同时提高活性位点暴露、界面电荷传输、OER反应动力学和抗Cl-腐蚀能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of water electrolysis technology and discloses a MOF-LDHs heterostructure catalyst, its preparation method, and its application. The preparation method of the catalyst includes the following steps: first, a layered nickel-iron bimetallic hydroxide is prepared on nickel foam using a hydrothermal method; then, it is immersed in an aqueous solution containing an organic carboxylic acid ligand, and reacted to obtain a NiFe-MOF / NiFe-LDHs (MOF-LDHs) heterostructure catalyst. The NiFe-MOF / NiFe-LDHs (MOF-LDHs) heterostructure catalyst prepared by this invention can effectively resist chloride ion corrosion, achieving excellent activity and long-term stability in the oxygen evolution reaction at high current densities, while also maintaining low preparation costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water electrolysis technology, and specifically relates to a MOF-LDHs heterostructure catalyst, its preparation method, and its application. Background Technology

[0002] With increasing environmental pollution, energy shortages, and carbon emissions, developing clean, efficient, and sustainable energy conversion and storage technologies has become a crucial direction for the energy sector. Hydrogen energy, with its high energy density, wide availability, and clean usage, is considered an important secondary energy source to replace traditional fossil fuels and promote the construction of a green and low-carbon energy system. Currently, industrial hydrogen production still mainly relies on fossil fuel reforming and industrial by-product hydrogen production. These processes not only consume non-renewable fossil resources but also generate large amounts of carbon dioxide and pollutants, hindering the achievement of "dual carbon" goals (carbon reduction and emission reduction). In contrast, water electrolysis can utilize renewable electricity to convert water into high-purity hydrogen, representing a significant technological path for large-scale green hydrogen production. However, traditional water electrolysis relies heavily on freshwater resources, which are limited globally and cannot meet future large-scale hydrogen production demands. Seawater is abundant and widely distributed; direct seawater electrolysis for hydrogen production holds promise for alleviating freshwater resource depletion and has significant application potential. However, natural seawater has a complex composition, containing large amounts of Cl-. - Mg 2+ Ca 2+ And other inorganic salt ions. During the oxygen evolution reaction at the anolyte, Cl... - It can not only corrode electrode materials, but may also compete with the oxygen evolution reaction (OER), triggering chlorine evolution reaction or hypochlorite formation reaction, thereby reducing oxygen evolution selectivity, energy conversion efficiency and electrode lifespan.

[0003] Currently, OER catalysts for seawater electrolysis mainly include noble metal-based catalysts and non-noble metal-based catalysts. While noble metal-based catalysts such as Ru and Ir exhibit high catalytic activity, their resources are scarce and expensive, and they are still susceptible to dissolution, reconstruction, and deactivation under high current densities and chlorine-containing environments, limiting their large-scale application. In contrast, non-noble metal catalysts such as NiFe-based oxides, hydroxides, and hydroxyl oxides have advantages such as abundant resources, low cost, tunable electronic structure, and high alkaline OER activity, attracting widespread attention in the field of seawater electrolysis. However, existing NiFe-based catalysts still suffer from insufficient reaction kinetics, limited utilization of active sites, and Cl... - Competitive adsorption and corrosion lead to problems such as decreased stability.

[0004] Therefore, developing catalysts that combine high OER activity, high oxygen evolution selectivity, and excellent resistance to chlorine corrosion is key to achieving efficient and stable hydrogen production from seawater electrolysis. Summary of the Invention

[0005] This invention aims to solve at least one of the technical problems existing in the prior art. To this end, this invention proposes a MOF-LDHs heterostructure catalyst, its preparation method, and its applications. This catalyst can effectively resist chloride ion attack, achieving excellent activity and long-term stability in the oxygen evolution reaction at high current densities, while also maintaining low preparation costs.

[0006] A first aspect of the present invention provides a method for preparing a catalyst, comprising the following steps: (1) Dissolve soluble iron salt, soluble nickel salt, urea and ammonium salt in water to prepare a mixed solution; then immerse foamed nickel in the mixed solution to carry out a hydrothermal reaction to obtain layered nickel-iron bimetallic hydroxide, denoted as NiFe-LDHs; (2) Prepare an aqueous solution containing organic carboxylic acid ligands and adjust the pH to alkaline; (3) The NiFe-LDHs are immersed in the aqueous solution containing the organic carboxylic acid ligand and reacted. After the in-situ self-dissociation of the transition metal element in NiFe-LDHs and the coordination self-assembly of the organic carboxylic acid ligand and the transition metal element, the NiFe-MOF / NiFe-LDHs heterostructure catalyst is obtained, namely the catalyst.

[0007] Specifically, this invention places layered NiFe-LDHs hydroxides prepared by a hydrothermal method in an aqueous solution containing organic carboxylic acid ligands. Heterostructured nanosheets composed of NiFe-LDHs and NiFe-MOF with organic carboxylic acid ligands are constructed in situ on the surface of the NiFe-LDHs. Through the multilayered oxygen evolution reaction active sites and the repulsion effect of organic carboxylic acid ions on chloride ions, the intrinsic catalytic activity and chloride resistance are simultaneously improved. The NiFe-MOF / NiFe-LDHs heterostructure catalyst prepared by this invention shows excellent application prospects for industrial water electrolysis to produce hydrogen.

[0008] In some embodiments of the present invention, the soluble nickel salt includes at least one of nickel chloride, nickel nitrate, nickel sulfate, and nickel oxalate.

[0009] In some embodiments of the present invention, the concentration of the soluble nickel salt in the mixed solution is 0.01-0.5 mol / L. Specifically, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or any value between them.

[0010] In some embodiments of the present invention, the soluble iron salt includes at least one of ferric chloride, ferric nitrate, ferric sulfate, and ferric oxalate.

[0011] In some embodiments of the present invention, the concentration of the soluble iron salt in the mixed solution is 0.002-0.5 mol / L. Specifically, it can be 0.01 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or any value between them.

[0012] In some embodiments of the present invention, the ammonium salt includes at least one of ammonium chloride, ammonium fluoride, and ammonium bromide.

[0013] In some embodiments of the present invention, the concentration of the ammonium salt in the mixed solution is 0.1-0.7 mol / L. Specifically, it can be 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, or any value between them.

[0014] In some embodiments of the present invention, the concentration of urea in the mixed solution is 0.1-3.5 mol / L. Specifically, it can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L; or any value between them.

[0015] In some embodiments of the present invention, the molar ratio of the total amount of the soluble nickel salt and the soluble iron salt to the ammonium salt is 1:(1-3). For example, it can be 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8; or any value between them.

[0016] In some embodiments of the present invention, the molar ratio of the ammonium salt to urea is 1:(1-5). For example, it can be 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4; or any value between them.

[0017] In some embodiments of the present invention, the organic carboxylic acid ligand includes at least one selected from 2,6-naphthoic acid, 4,4′-dihydroxybiphenyl-3,3′-dicarboxylic acid, aminoterephthalic acid, 2,5-dihydroxyterephthalic acid, 4,4′-biphenylic acid, and 4,6-dihydroxyisophthalic acid.

[0018] In some embodiments of the present invention, the concentration of the organic carboxylic acid ligand in the aqueous solution containing the organic carboxylic acid ligand is 1-20 mmol / L. For example, it can be 2 mmol / L, 5 mmol / L, 8 mmol / L, 10 mmol / L, 12 mmol / L, 15 mmol / L; or any value between them.

[0019] In some embodiments of the present invention, the pH of the aqueous solution containing the organic carboxylic acid ligand is 7.5-9.0. Specifically, it can be 8.0, 8.2, 8.5, 8.8, or any value between them.

[0020] In some embodiments of the present invention, in step (1), the temperature of the hydrothermal reaction is 80-170°C. For example, it can be 100°C, 120°C, 140°C, 160°C, or any value between them.

[0021] In some embodiments of the present invention, in step (1), the hydrothermal reaction time is 4-16 hours. For example, it can be 6 hours, 8 hours, 10 hours, 12 hours, 14 hours; or any value between them.

[0022] In some embodiments of the present invention, in step (2), the reagent used to adjust the pH includes at least one of ammonia, sodium hydroxide and potassium hydroxide.

[0023] In some embodiments of the present invention, in step (3), the temperature of the reaction is 20-60°C. For example, it can be 30°C, 40°C, 50°C; or any value between them.

[0024] In some embodiments of the present invention, the reaction time in step (3) is 0.5-16 hours. For example, it can be 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours; or any value between them.

[0025] In some embodiments of the present invention, in step (1), the nickel foam is pretreated before being immersed in the mixed solution. The pretreatment includes washing with hydrochloric acid, anhydrous ethanol and water in sequence to remove oxides from the surface of the nickel foam.

[0026] In some embodiments of the present invention, step (3) further includes washing the reaction product with water and anhydrous ethanol and drying it after the reaction is completed.

[0027] In some embodiments of the present invention, the drying temperature is 50-90°C. Specifically, it can be 60°C, 70°C, 80°C, or any value between them.

[0028] In some embodiments of the present invention, the drying time is 4-24 hours. Specifically, it can be 6 hours, 8 hours, 10 hours, 12 hours, 15 hours, 20 hours; or any value between them.

[0029] In a second aspect, the present invention provides a catalyst prepared by the preparation method described in the first aspect of the present invention, the catalyst comprising a nickel foam support and a NiFe-MOF / NiFe-LDHs heterostructure catalyst supported on the nickel foam support.

[0030] A third aspect of the invention provides the application of the catalyst described in the second aspect of the invention in the electrolysis of seawater.

[0031] In some embodiments of the present invention, the electrolysis of seawater is carried out in a three-electrode system, wherein KOH and seawater are used as electrolytes, the catalyst described in the present invention is used as the working electrode, Hg / HgO is used as the reference electrode, and a carbon rod electrode is used as the counter electrode.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention is based on metal-organic framework (MOF) materials, especially NiFe-MOF formed by the coordination of organic carboxylic acid ligands with Ni and Fe metal sites, which has the characteristics of tunable structure, large specific surface area, high metal center dispersion and designable coordination environment; at the same time, NiFe-LDHs have good alkaline OER activity and structural stability; this invention utilizes organic carboxylic acid ligands to induce coordination reconstruction of metal sites on the surface of NiFe alloy under mild conditions, and further forms a heterostructure of NiFe-MOF and NiFe-LDHs to prepare NiFe-MOF / NiFe-LDHs heterostructure catalyst, which can simultaneously improve active site exposure, interfacial charge transport, OER reaction kinetics and resistance to Cl. - Corrosion resistance.

[0033] (2) The catalyst prepared by this invention only requires an overpotential of 282 mV to reach 1000 mA·cm. -2 The current density was measured, and stable operation was maintained at this current density for 1500 hours. Therefore, the simple preparation method of NiFe-MOF / NiFe-LDHs heterostructure catalyst based on in-situ construction of organic carboxylic acid ligands provided by this invention is of great significance for realizing a low-cost, high-activity, and high-stability seawater oxygen evolution electrode. Attached Figure Description

[0034] Figure 1 The XRD patterns are of the catalysts prepared in Example 2 and Comparative Example 1. Figure 2 The image shows a SEM image of the catalyst prepared in Comparative Example 1. Figure 3 Here is a SEM image of the catalyst prepared in Example 2; Figure 4 The polarization curves of the catalysts prepared in Example 2 and Comparative Examples 1-3 in alkaline seawater are shown. Figure 5 The polarization curves of the catalysts prepared in Examples 1-3 in alkaline seawater are shown. Figure 6 The catalyst prepared in Example 2 was tested in alkaline seawater at 1000 mA·cm⁻¹. -2 Oxygen evolution stability test graph at current density. Detailed Implementation

[0035] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments can be obtained from conventional commercial sources or by existing technical methods. Unless otherwise specified, the experimental or testing methods are conventional methods in the art.

[0036] Example 1 This embodiment provides a method for preparing a NiFe-MOF / NiFe-LDHs heterostructure catalyst, including the following steps: (1) The nickel foam carrier was ultrasonically cleaned in hydrochloric acid (concentration of 3 mol / L), anhydrous ethanol and deionized water for 20 minutes in sequence, and then dried in a vacuum oven at 60°C for 12 hours for later use.

[0037] (2) Weigh 2.5 mmol of nickel nitrate, 0.5 mmol of ferric nitrate, 4 mmol of ammonium fluoride and 10 mmol of urea and dissolve them in 35 mL of deionized water and stir evenly to obtain a mixed solution; then place the foamed nickel in the mixed solution, transfer it to the reaction vessel, heat it to 120 °C in the oven and carry out a hydrothermal reaction for 10 hours; after the reaction is completed, wash it repeatedly with deionized water and anhydrous ethanol three times in sequence, and dry it at 60 °C for 12 hours to obtain layered nickel-iron bimetallic hydroxide, denoted as NiFe-LDHs.

[0038] (3) Dissolve 100 mmol of 2,6-naphthalenedicarboxylic acid in a certain volume of deionized water and stir thoroughly with a magnetic stirrer. Then adjust the pH of the solution to 8.5 with 2M KOH and make the concentration of 2,6-naphthalenedicarboxylic acid 5 mol / L.

[0039] (4) The NiFe-LDHs obtained in step (2) is placed in the 2,6-naphthalenedicarboxylic acid aqueous solution with a concentration of 5 mol / L prepared in step (3) and soaked at 30°C for 10 hours. Then the product is washed repeatedly with deionized water and ethanol three times in sequence and dried at 60°C for 12 hours to obtain the NiFe-MOF / NiFe-LDHs heterostructure catalyst of this embodiment, denoted as MOF-LDHs.

[0040] Example 2 This embodiment provides a method for preparing a NiFe-MOF / NiFe-LDHs heterostructure catalyst, including the following steps: (1) The foamed nickel carrier was ultrasonically cleaned in hydrochloric acid (concentration of 3 mol / L), anhydrous ethanol and deionized water for 25 minutes in sequence, and then dried in a vacuum oven at 60°C for 12 hours for later use.

[0041] (2) Weigh 3 mmol of nickel nitrate, 1 mmol of ferric nitrate, 5 mmol of ammonium fluoride and 10 mmol of urea and dissolve them in 35 mL of deionized water and stir evenly to obtain a mixed solution; then place the foamed nickel in the mixed solution, transfer it to the reaction vessel, heat it to 125 °C in the oven and carry out a hydrothermal reaction for 7 hours; after the reaction is completed, wash it repeatedly with deionized water and anhydrous ethanol 3 times in sequence, and dry it at 70 °C for 10 hours to obtain layered nickel-iron bimetallic hydroxide, denoted as NiFe-LDHs.

[0042] (3) Dissolve 140 mmol of 4,4'-biphenyldicarboxylic acid in a certain volume of deionized water and stir thoroughly with a magnetic stirrer. Then adjust the pH of the solution to 9.0 with 3M NaOH and make the concentration of 4,4'-biphenyldicarboxylic acid 7 mol / L.

[0043] (4) The NiFe-LDHs obtained in step (2) is placed in the 7 mol / L aqueous solution of 4,4'-biphenyl dicarboxylic acid prepared in step (3) and soaked at 30°C for 10 hours. Then the product is washed repeatedly with deionized water and ethanol three times in sequence and dried at 60°C for 12 hours to obtain the NiFe-MOF / NiFe-LDHs heterostructure catalyst of this embodiment, denoted as MOF-LDHs.

[0044] Example 3 This embodiment provides a method for preparing a NiFe-MOF / NiFe-LDHs heterostructure catalyst, including the following steps: (1) The foamed nickel carrier was ultrasonically cleaned for 15 minutes in hydrochloric acid (concentration of 4 mol / L), anhydrous ethanol and deionized water respectively, and then dried in a vacuum oven at 50°C for 12 hours for later use.

[0045] (2) Weigh 3 mmol of nickel nitrate, 1 mmol of ferric nitrate, 5 mmol of ammonium fluoride and 10 mmol of urea and dissolve them in 35 mL of deionized water and stir evenly to obtain a mixed solution; then place the foamed nickel in the mixed solution, transfer it to the reaction vessel, heat it to 125 °C in the oven and carry out a hydrothermal reaction for 7 hours; after the reaction is completed, wash it repeatedly with deionized water and anhydrous ethanol 3 times in sequence, and dry it at 70 °C for 10 hours to obtain layered nickel-iron bimetallic hydroxide, denoted as NiFe-LDHs (LDHs).

[0046] (3) Dissolve 180 mmol of 4,4′-dihydroxybiphenyl-3,3′-dicarboxylic acid in a certain volume of deionized water and stir thoroughly with a magnetic stirrer. Then adjust the pH of the solution to 9.0 with 3M NaOH and make the concentration of 4,4′-dihydroxybiphenyl-3,3′-dicarboxylic acid 8 mol / L.

[0047] (4) The NiFe-LDHs (LDHs) obtained in step (2) were placed in an aqueous solution of 4,4′-dihydroxybiphenyl-3,3′-dicarboxylic acid with a concentration of 8 mol / L prepared in step (3), and soaked at 25°C for 12 hours. Then the product was washed repeatedly with deionized water and ethanol three times in sequence, and dried at 70°C for 10 hours to obtain the NiFe-MOF / NiFe-LDHs heterostructure catalyst of this embodiment, denoted as MOF-LDHs.

[0048] Comparative Example 1 A method for preparing a NiFe-LDHs catalyst includes the following steps: (1) The foamed nickel carrier was ultrasonically cleaned in hydrochloric acid (concentration of 3 mol / L), anhydrous ethanol and deionized water for 25 minutes in sequence, and then dried in a vacuum oven at 60°C for 12 hours for later use.

[0049] (2) Weigh 3 mmol of nickel nitrate, 1 mmol of ferric nitrate, 5 mmol of ammonium fluoride and 10 mmol of urea and dissolve them in 35 mL of deionized water and stir evenly to obtain a mixed solution; then place the foamed nickel in the mixed solution, transfer it to the reaction vessel, heat it to 125 °C in the oven and carry out a hydrothermal reaction for 7 hours; after the reaction is completed, wash it repeatedly with deionized water and anhydrous ethanol 3 times in sequence, and dry it at 70 °C for 10 hours to obtain layered nickel-iron bimetallic hydroxide, denoted as NiFe-LDHs (LDHs).

[0050] Comparative Example 2 A method for preparing a RuO2 catalyst includes the following steps: 5 mg of RuO2 powder and 50 μL of 5 wt% Nafion solution were dispersed in 950 μL of anhydrous ethanol and sonicated for 15 min to obtain a homogeneous mixture. Then, 160 μL of the mixture was dropped onto a surface with an area of ​​0.3 cm². 2 RuO2 catalyst was prepared by drying the foamed nickel in a vacuum drying oven at 50°C.

[0051] Comparative Example 3 The nickel foam carrier was ultrasonically cleaned in hydrochloric acid (3 mol / L), anhydrous ethanol, and deionized water for 25 minutes in sequence, and then dried in a vacuum oven at 60°C for 12 hours. This was denoted as NF.

[0052] Performance testing 1. Microstructure Figure 1 The images show the XRD patterns of the NiFe-MOF / NiFe-LDHs (MOF-LDHs) catalyst prepared in Example 2 and the MOF-LDHs catalyst prepared in Comparative Example 1, where the horizontal axis 2Theta represents the diffraction angle 2θ, and the vertical axis Intensity represents the intensity of the diffraction peak. Figure 1 It can be observed that the prepared samples are consistent with the standard card (PDF#40-0215) of NiFe-LDHs (LDHs), and no new phases were found. Moreover, the XRD patterns show that no new phases appeared in MOF-LDHs, which may be due to the relatively low content of NiFe-MOF layers.

[0053] Figure 2 SEM image of NiFe-LDHs (LDHs) prepared in Comparative Example 1; Figure 3 The image shows a SEM image of the MOF-LDHs prepared in Example 2. Figure 2 and Figure 3 Both catalysts exhibit a nanosheet structure.

[0054] 2. Electrochemical performance The catalysts prepared in the above examples and comparative examples were directly used as working electrodes in the electrocatalytic oxygen evolution reaction. The specific testing process was as follows: An alkaline seawater solution containing 1 mol / L KOH and 0.5 mol / L NaCl was prepared as the electrolyte for electrocatalysis. Nitrogen gas was bubbled through the solution at a rate of 20 mL / min for 30 min until the solution was saturated with nitrogen. A three-electrode system was assembled using the catalysts prepared in the above examples and comparative examples as the working electrode, an Hg / HgO electrode as the reference electrode, and a carbon rod electrode as the counter electrode. Electrochemical performance was then tested on an electrochemical workstation.

[0055] Figure 4The graphs show the polarization curves of MOF-LDHs, NiFe-LDHs, RuO2, and NF prepared in Examples 2 and Comparative Examples 1-3 in alkaline seawater, where the horizontal axis represents voltage and the vertical axis represents current density. Figure 4 It can be seen that the MOF-LDHs catalyst prepared in Example 2 exhibits excellent OER performance, requiring only relatively low overpotentials of 233mV, 262mV, 282mV, and 305mV to achieve 100, 500, 1000, and 2000 mA·cm⁻¹, respectively. -2 The current density of the sample is significantly better than that of NiFe-LDHs, RuO2 and NF prepared in Comparative Examples 1-3, which indicates that the heterostructure formed by NiFe-MOF and NiFe-LDHs can significantly improve its oxygen evolution catalytic activity.

[0056] Figure 5 The graphs show the polarization curves of the MOF-LDHs catalysts prepared in Examples 1-3 (corresponding to Cases 1-3 in the figures) in alkaline seawater. Figure 5 It can be seen that the MOF-LDHs catalyst prepared in Example 2 exhibits high OER catalytic activity in alkaline seawater.

[0057] Figure 6 The catalyst prepared in Example 2 was tested in an alkaline seawater solution at 1000 mA·cm⁻¹. -2 Results of oxygen evolution stability tests at current density. Figure 6 It can be seen that the MOF-LDHs catalyst prepared in Example 2 exhibits excellent stability at 1000 mA·cm⁻¹. -2 Stable operation for over 1500 hours at industrial-grade current densities. This is attributed to the fact that during the oxygen evolution reaction (OER), NiFe-MOF provides coordination protection, pore and structural constraints for carboxylic acids, while NiFe-LDHs provide highly active reconstructed parent material and OH groups. - Transport interface; electronic coupling between the two phases promotes the formation of the NiFeOOH active layer, while reducing Cl... - Adsorption, metal dissolution, and structural collapse enhance the catalyst's resistance to chlorine corrosion and its structural stability.

[0058] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention, and these equivalent modifications or substitutions are all included within the scope defined by the claims of this application.

Claims

1. A method for producing a catalyst, characterized by, Includes the following steps: (1) Dissolve soluble iron salt, soluble nickel salt, urea and ammonium salt in water to prepare a mixed solution; then immerse foamed nickel in the mixed solution to carry out a hydrothermal reaction to obtain layered nickel-iron bimetallic hydroxide, denoted as NiFe-LDHs; (2) Prepare an aqueous solution containing organic carboxylic acid ligands and adjust the pH to alkaline; (3) The NiFe-LDHs are immersed in the aqueous solution containing the organic carboxylic acid ligand and reacted to obtain the NiFe-MOF / NiFe-LDHs heterostructure catalyst, i.e. the catalyst.

2. The preparation method according to claim 1, characterized in that, The organic carboxylic acid ligand includes at least one of 2,6-naphthalenedicarboxylic acid, 4,4′-dihydroxybiphenyl-3,3′-dicarboxylic acid, aminoterephthalic acid, 2,5-dihydroxyterephthalic acid, 4,4′-biphenylic acid, and 4,6-dihydroxyisophthalic acid.

3. The preparation method according to claim 1, characterized in that, The concentration of the organic carboxylic acid ligand in the aqueous solution containing the organic carboxylic acid ligand is 1-20 mmol / L.

4. The preparation method according to claim 1, characterized in that, The aqueous solution containing the organic carboxylic acid ligand has a pH of 7.5-9.

0.

5. The preparation method according to claim 1, characterized in that, In step (1), the temperature of the hydrothermal reaction is 80-170℃; and / or the time of the hydrothermal reaction is 4-16 hours.

6. The preparation method according to claim 1, characterized in that, In step (3), the temperature of the reaction is 20-60°C; and / or the reaction time is 0.5-16 hours.

7. The preparation method according to claim 1, characterized in that, The soluble nickel salt includes at least one of nickel chloride, nickel nitrate, nickel sulfate, and nickel oxalate; and / or, the soluble iron salt includes at least one of ferric chloride, ferric nitrate, ferric sulfate, and ferric oxalate; and / or, the ammonium salt includes at least one of ammonium chloride, ammonium fluoride, and ammonium bromide.

8. The preparation method according to claim 1, characterized in that, The total amount of the soluble nickel salt and soluble iron salt in the molar ratio of the ammonium salt is 1:(1-3); and / or, the molar ratio of the ammonium salt to urea is 1:(1-5).

9. A catalyst, characterized in that, The catalyst is prepared by the preparation method according to any one of claims 1-8, and the catalyst comprises a nickel foam support and a NiFe-MOF / NiFe-LDHs heterostructure catalyst supported on the nickel foam support.

10. The application of the catalyst according to claim 9 in the electrolysis of seawater.